The stationary transversr Euler and Stokes gas flows through a cylindrical region wilii large variations of density and viscosity coefficient - Płochocki, Z.; Kaźmierczak, B. (Archives of Mechanics, 1996)
The flow of a gas in space, which encounters a cylindrical region, where the density of the gas (and its viscosity coefficient) changes abruptly, is considered both in the Euler and the Stokes approximations. The flow is homogeneous at infinity. Density and viscosity coefficients of the gas are assumed to be constants, which are different outside and inside the cylinder. The analytical solutions of the problem are found in both cases. These solutions may be useful for building the models of flow in flames or laser-sustained (or generated) plasmas.